LA EVOLUCIÓN DEL URBANISMO DE ÉCIJA (SEVILLA): de la Tardoantigüedad a la época islámica - Becerra Fernández, Daniel (2015)
With this article we address the general aspects of the transition between late antiquity and the early Middle Ages in the city of Ecija, addressing its most significant aspects and analyze its evolution since its configuration as a Roman city until its transformation into an Islamic city.